ANALISIS KELAYAKAN BUKU TEKS FIKSI PUISI KELAS VIII SMP NEGERI 7 MEDAN - Khoirunnisa Mei Desiani; Muhammad Surip; Malan Lubis (BAHAS, 2023)
Abstract The research objective of this scientific article is to determine the feasibility of poetry fiction textbooks. The source of data in this research is the Indonesian language teacher. Data collection techniques used are primary data and secondary data. The primary data is in the form of analysis of student textbooks. Meanwhile, secondary data consists of books, articles, journals, and other sources that are relevant to the research problem. The data analysis technique uses a descriptive technique with the following steps: a) Analyzing data sources in the form of interviews with Indonesian teachers and written discourse in Indonesian language textbooks for junior high school level. b) Describe the material contained in the book. c) Assessing the quality of the book by using the content and language appropriateness test in the poetry material. d) Drawing conclusions. From the analysis of the data, it can be seen that the textbooks for Indonesian language students, especially in the poetry material presented, are not entirely perfect. The researcher found that aspects of the book's content and language aspects of the book did not support student creativity. Keywords: Feasibility of Textbooks, Poetry Fictional TextsAbstrak Tujuan penelitian artikel ilmiah ini adalah untukmengetahui kelayakan buku teks fiksi puisi.Sumber data dalam penelitian adalah guru bahasa Indonesia. Teknikpengumpulandatayangdigunakanadalah data primer dan data sekunder. Data primer berupa analisis buku teks siswa. Sedangkan data sekunder berpa buku-buku, artikel, jurnal, dan sumber lain yang relevan dengan masalah dalam penelitian.Teknikanalisisdata menggunakan teknik deskriptif dengan langkah-langkah: a) Menganalis sumber data berupa hasil wawancara terhadap guru bahasa Indonesia dan wacana tertulis dalam buku teks bahasa Indonesia untuk jenjang SMP. b) Mendeskripsikan materi yang terdapat dalam buku. c) Melakukan penilaian kualitas buku dengan menggunakan uji kelayakan isi dan bahasa dalam materi puisi. d) Mengambil kesimpulan. Dari analisis data tersebut bahwa buku teks siswa bahasa Indoensia terutama dalam materi puisi yang tersaji belum seluruhnya sempurna. Peneliti menemukan aspek isi buku dan aspek bahasa buku tersebut belum menunjang kreativitas siswa. Kata kunci: Kelayakan Buku Teks, Teks Fiksi Puisi Abstract The research objective of this scientific article is to determine the feasibility of poetry fiction textbooks. The source of data in this research is the Indonesian language teacher. Data collection techniques used are primary data and secondary data. The primary data is in the form of analysis of student textbooks. Meanwhile, secondary data consists of books, articles, journals, and other sources that are relevant to the research problem. The data analysis technique uses a descriptive technique with the following steps: a) Analyzing data sources in the form of interviews with Indonesian teachers and written discourse in Indonesian language textbooks for junior high school level. b) Describe the material contained in the book. c) Assessing the quality of the book by using the content and language appropriateness test in the poetry material. d) Drawing conclusions. From the analysis of the data, it can be seen that the textbooks for Indonesian language students, especially in the poetry material presented, are not entirely perfect. The researcher found that aspects of the book's content and language aspects of the book did not support student creativity. Keywords: Feasibility of Textbooks, Poetry Fictional TextsAbstrak Tujuan penelitian artikel ilmiah ini adalah untukmengetahui kelayakan buku teks fiksi puisi.Sumber data dalam penelitian adalah guru bahasa Indonesia. Teknikpengumpulandatayangdigunakanadalah data primer dan data sekunder. Data primer berupa analisis buku teks siswa. Sedangkan data sekunder berpa buku-buku, artikel, jurnal, dan sumber lain yang relevan dengan masalah dalam penelitian.Teknikanalisisdata menggunakan teknik deskriptif dengan langkah-langkah: a) Menganalis sumber data berupa hasil wawancara terhadap guru bahasa Indonesia dan wacana tertulis dalam buku teks bahasa Indonesia untuk jenjang SMP. b) Mendeskripsikan materi yang terdapat dalam buku. c) Melakukan penilaian kualitas buku dengan menggunakan uji kelayakan isi dan bahasa dalam materi puisi. d) Mengambil kesimpulan. Dari analisis data tersebut bahwa buku teks siswa bahasa Indoensia terutama dalam materi puisi yang tersaji belum seluruhnya sempurna. Peneliti menemukan aspek isi buku dan aspek bahasa buku tersebut belum menunjang kreativitas siswa. Kata kunci: Kelayakan Buku Teks, Teks Fiksi Puisi